PERBEDAAN SKOR SINO NASAL OUTCOME TEST 22 SEBELUM DAN SESUDAH TERAPI LARUTAN HIPERTONIK DAN ISOTONIK PADA PASIEN RINOSINUSITIS KRONIS - LISTI SURYANI; SITI MASLIANI SIREGAR (JURNAL ILMIAH KOHESI, 2021)
Chronic rhinosinusitis has a high prevalence in the world community. According to the European Position Paper onRhinosinusitis and Nasal Polyps 2012 (EPOS) which is as much as 10.9% with geographical variations of chronicrhinosinusitis significantly reduces the quality of life of patients due to symptoms that usually appear. For chronic diseasessuch as rhinosinusitis, the quality of life of sufferers is important in monitoring the severity of the disease. Studies show thatmore than 75% of patients with chronic rhinosinusitis have a poor quality of life according to the severity of rhinosinusitis.The recommended therapy for the European Position Paper on Rhinosinusitis and Nasal Polyps 2012 (EPOS 2012) forchronic rhinosinusitis is nasal washers. Researchers are interested in seeing differences SNOT score of 22 before and afteradministration of hypertonic and isotonic solutions of patients with chronic rhinosinusitis. This study aims to determinedifferences in sino nasal outcome test scores 22 before and after administration of hypertonic and isotonic solutions inpatients with chronic rhinosinusitis. This study uses a purely experimental method with a Randomized Control Trial Pre andPost Test Design. The study population was all patients with chronic rhinosinusitis. Overall, for two weeks of therapy, 20hypertonic respondents were found, out of 20 of them with good quality of life while 20 isotonic respondents, 19 with goodquality of life and 1 with poor quality of life based on McNemar test results, p value = 0,000 < 0.05, it is concluded that thereis a significant difference between the administration of live washing hypertonic and isotonic solutions. Hypertonic andisotonic saline solution is effective in reducing the level of clinical symptoms complaints of patients with chronic rhinosinusitis.